An assessment of the sustainability of substance abuse organisations in South Africa - Mawoyo, Tatenda (Department of Social Development, 2015)
This research study sought to explore the sustainability of organisations in the field of substance abuse in South Africa. The rationale of this study was based on the premise that the number of substance abusers is increasing, therefore the organisations have to remain functional to deal with the increased demand of services. The study explored the financial position of organisations in the field, perceptions regarding policy and legislation, staff related effects of working in the field, factors that make organisations vulnerable to closure and sustainability threats.